Clinical pathogenesis of typhoid fever - Raffatellu, Manuela; Wilson, R. Paul; Winter, Sebastian E.; Baumler, Andreas J. (The Journal of Infection in Developing Countries, 2008)
Human infections with Salmonella enterica results in two major groups of diseases: gastroenteritis and typhoid fever. Clinical observations suggest that gastroenteritis, caused by non-typhoidal Salmonella serovars, is characterized by a massive neutrophil influx, which keeps the infection localized to the intestinal mucosa. In contrast, the absence of neutrophilic intestinal infiltrates in the acute phase of typhoid fever suggests a propensity for typhoidal Salmonella serovars (S. Typhi, S. Paratyphi A, S. Paratyphi B and S. Paratyphi C) to evade aspects of the innate immune response and cause a systemic infection. The fact that there are no virulence genes shared by typhoidal Salmonella serovars that are absent from non-typhoidal Salmonella serovars, suggests that this innate immune evasion is mediated by different mechanisms in different typhoidal serovars. This review discusses what is known about the clinical pathogenesis of typhoid fever.